Genotypes of Sechium spp. as a Source of Natural Products with Biological Activity - Jorge Cadena-Iñiguez; Ma. de Lourdes Arévalo-Galarza; Edelmiro Santiago-Osorio; Itzen Aguiñiga-Sánchez; Jorge David Cadena-Zamudio; Marcos Soto-Hernández; Yeimy C. Ramírez-Rodas; Lucero del Mar Ruiz-Posadas; Sandra Salazar-Aguilar; Víctor Manuel Cisneros-Solano (Life)
The genus Sechium P. Br. (Cucurbitaceae) includes ten species, two of which are edible. The inedible genotypes are in a fragile ecological niche, since they are not used by rural inhabitants. A rescue and genetic crossing program was designed to identify uses that favor their conservation due to their content of bioactive secondary metabolites (Sm) for health. Fruits of S. compositum (wild type), hybrid H-D Victor (inedible), and S. edule var. nigrum spinosum (edible) were evaluated by extraction methods such as juice and oven drying to determine the yields of Sm, with in vivo evaluations of liver damage. The dried biomass (40 °C) extracted with ethanolic and methanolic procedures showed lower Sm content than the juice (fresh biomass). More than 90% of phenolic acids and cucurbitacins in the extracts were degraded, possibly due to the drying time (oven). Biological activity showed that nigrum spinosum and HD-Victor have fewer toxic metabolites than S. compositum. The hybrid H-D Victor is of reduced cytotoxicity, showing the advantages of hybridization with wild types. Phytochemical and biological activity characterization may contribute to the conservation of genotypes and become a source of bioactive natural products.